CD24, not CD47, negatively impacts upon response to PD‐1/L1 inhibitors in non–small‐cell lung cancer with PD‐L1 tumor proportion score < 50. Issue 1 (27th November 2020) - Ozawa, Yuichi; Harutani, Yuhei; Oyanagi, Jun; Akamatsu, Hiroaki; Murakami, Eriko; Shibaki, Ryota; Hayata, Atsushi; Sugimoto, Takeya; Tanaka, Masanori; Takakura, Toshiaki; Furuta, Katsuyuki; Okuda, Yuka; et al.
Abstract: CD24, a heavily glycosylated glycosylphosphatidylinositol–anchored surface protein, inhibits phagocytosis as potently as CD47. The relationship between such anti‐phagocytic factors and the immune response with immune–checkpoint inhibitors (ICI) remains unexplored. We evaluated CD24 and CD47 tumor proportion scores (TPS) in 68 of the 106 patients with advanced non–small‐cell lung cancer who participated in a prospective observational study of ICI treatment. We also explored the impact of CD24 TPS and CD47 TPS on ICI efficacy and serum cytokine changes. CD24 positivity (TPS ≥ 1) was negatively associated with progression–free survival (PFS) of ICI when PD‐L1 TPS was < 50 (median PFS; 37 vs 127 d, P = .033), but there was no association when PD‐L1 TPS was ≥ 50 (median PFS; 494 vs 144 d, P = .168). CD24 positivity was also related to significantly higher increase of CCL2 from baseline to 4‐6 wk later, and such increase was notably observed only when PD‐L1 TPS < 50 ( P = .0004). CCL2 increase after ICI initiation was negatively predictive for survival after initiation of ICI (median survival time; not reached vs 233 d; P = .028). CD47 TPS high (≥60) significantly suppressed the increase in vascular endothelial growth factor (VEGF)‐A, D and PDGF‐AB/BB after ICI initiation. There was no association, however, between CD47 tumor expression and the efficacy of ICI. In conclusion, CD24, not CD47, is a candidate negative predictive marker of ICI in advanced, non–small‐cell lung cancer with PD‐L1 TPS < 50. Tumor expression of both CD24 and CD47 was associated with changes in factors related to monocytes and angiogenesis after ICI initiation (UMIN000024414). Abstract : We evaluated tumor proportion score (TPS) of CD24 and CD47 in 68 patients with advanced, non–small‐cell lung cancer who participated in a prospective observational study for treatment with ICI, and we also explored the impact of CD24 TPS and CD47 TPS on the efficacy of ICI and serum cytokine alterations. CD24 positivity (TPS ≥ 1) was negatively associated with progression–free survival of ICI when PD‐L1 TPS < 50 (median PFS; 37 vs 127 d, P = .033), but there was no association between CD47 tumor expression and the efficacy of ICI. CD24 positivity was also related to significantly higher increases in CCL2 from baseline to 4‐6 wk later, and such increase was notably observed only when PD‐L1 TPS was < 50 ( P = .0004).